Validating the Hornik & Woolf approach to choosing media campaign themes: Do promising beliefs predict behavior change in a longitudinal study? - Hornik, Robert C. (Commun Methods Meas, 2018)
Hornik and Woolf (1999) proposed using cross-sectional survey data to prioritize beliefs to address with communication campaign messages. The empirical component of the approach combines evidence of (1) association of beliefs with intentions and (2) current level of beliefs to calculate a ‘percentage to gain’ as the potential promise of a belief. However, the method relies on cross-sectional data; its conclusions are open to challenge. Here, a panel study assesses whether the calculated promise of a belief actually predicts future behavior change. A nationally representative sample of 3,204 U.S. youth and young adults were interviewed twice, six months apart. Sixteen beliefs about the benefits and costs of smoking cigarettes are compared with regard to their percentage to gain (calculated from cross-sectional data) and their ability to account for subsequent cigarette use. A belief’s cross-sectional percentage to gain is substantially associated with its ability to predict subsequent behavior change (r=.53, p<.05).